Stock Return Volatility and the Determinants: An Empirical Study of the US Market - Hsu, Chia-Luan (2009)
This study investigates the stock return volatility in the U.S. equity market between 2000 and 2008. Several financial characteristics, including the P/E ratio, dividend yield, trading volume, leverage effect, and firm’s size are jointly, rather than individually, employed in the analyses based upon the fixed effect model. In consideration of the time varying behavior in the return variation, the GARCH (1, 1) model is used to capture the stock return volatility.